If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 23 = 3y + 2 Reorder the terms: 23 = 2 + 3y Solving 23 = 2 + 3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3y' to each side of the equation. 23 + -3y = 2 + 3y + -3y Combine like terms: 3y + -3y = 0 23 + -3y = 2 + 0 23 + -3y = 2 Add '-23' to each side of the equation. 23 + -23 + -3y = 2 + -23 Combine like terms: 23 + -23 = 0 0 + -3y = 2 + -23 -3y = 2 + -23 Combine like terms: 2 + -23 = -21 -3y = -21 Divide each side by '-3'. y = 7 Simplifying y = 7
| (X-12)-2x=3x+4 | | v/5-3=2 | | 4+3v=-2 | | 10t^3+13t-3=0 | | 0.0003x^2+0.1x-88=0 | | 6x-(2x+1)=19 | | 4x^2-9y^2+16x+54y-29=0 | | y=1E+7x+-0.11 | | (331/5)-(331/6)=X | | n(n-2)=8 | | 7z^2-z-8=0 | | (X-5)/(X-6)=56 | | (X-5)(X-6)=56 | | 5x^4/10 | | 1000x^2-100x=0 | | 6x+2y+3y=11 | | (D^4+4D^2)y=96x^2 | | 2x11/4=13 | | (5.6x+2)(5.6x-2)= | | 25x^2+9y^2-18y-216=0 | | (0.6x-1.28)(18x+8)= | | 72=4x-12 | | 2m(n+3)-m(2n+1)= | | 2e^x/8e^-x | | X+0.6x=250y | | -5x+10=14+(4+x) | | g+7f=16 | | 12=3*x | | 4x^2+x=44 | | 9x+-9y=27 | | f(x)=10x-18 | | 4x^2+x-44=0 |